Üç Boyutlu Sayısal Ortam Araçlarının Görsel İletişim Tasarımı Bağlamında Öğretimi: Bir Lisans Dersi Örneği - Tüker, Çetin (The Turkish Online Journal of Design Art and Communication, 2015)
In this study, design principles of a ‘three dimensional modeling and animation tool instruction’ have been studied in the context of visual communication design domain by analyzing the ‘Computer Animation and 3D modeling’ course. The course is designed based on constructivist and elaboration theories. Visual design modules have been designed with software instruction modules as an organic inseparable body. Two student groups attended the course as 35 and 15 people. Couse has been analyzed by using qualitative case study techniques and ‘design principles for three dimensional tool instruction instruction’ have been listed as: instruction, technical issues related with software and hardware, instructor, software interface, spatial visualization abilities, course duration and group issues.
Keywords: Üç Boyutlu Ortam; Yazılım Öğretimi; Proje Tabanlı Öğretim; Ayrıntılama Teorisi; Tasarım Eğitimi; Three Dimensional Environment; Elaboration Theory; Software Training; Software Teaching; Project Based Teaching; Design Thinking